2008
DOI: 10.1017/s002221510800203x
|View full text |Cite
|
Sign up to set email alerts
|

Hearing aids and tinnitus therapy: a 25-year experience

Abstract: Provision of hearing aids in patients with audiometrically demonstrable hearing loss can play a very important part in tinnitus control. The additional improvement in tinnitus control observed following introduction of programmable digital aids had a summative effect in the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 13 publications
3
71
0
5
Order By: Relevance
“…Trotter and Donaldson (2008) reported greater degree of tinnitus reduction in monaurally fitted participants. Thus, the potential reason for decrease of tinnitus impact on fitting the participants with monaural hearing aids may be due to the presentation of amplified sounds in the better ear thus causing sound enrichment and subsequent masking of their tinnitus.…”
Section: Paired T-test Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Trotter and Donaldson (2008) reported greater degree of tinnitus reduction in monaurally fitted participants. Thus, the potential reason for decrease of tinnitus impact on fitting the participants with monaural hearing aids may be due to the presentation of amplified sounds in the better ear thus causing sound enrichment and subsequent masking of their tinnitus.…”
Section: Paired T-test Resultsmentioning
confidence: 85%
“…As the population studied in the study was above 60 years, it may be a possibility that all the participants perceived their hearing problem as primary and tinnitus as secondary. Trotter & Donaldson (2008) also reported that the use of binaural hearing aid had significant correlation in reducing the tinnitus handicap. In present study, even though pseudo-binaural hearing aids were used, the impacts were similar to using binaural behind-the-ear hearing aids.…”
Section: Post-hearing Aid Fitting Thi Scoresmentioning
confidence: 93%
See 1 more Smart Citation
“…Increases in the auditory nerve activities are demonstrated with acoustic stimulations given with masking treatment in tinnitus related to mild to moderate hearing loss [3,24]. Some studies reported that after receiving a hearing aid, one half [25] to two thirds [26] of the tinnitus subjects reported improvement of their tinnitus. Schaette et al [2 ]examined the influence of acoustic stimulation treatments to a set of pure tones or narrow-band noises and chose the closed match within the stimulated frequency range.…”
Section: Discussionmentioning
confidence: 99%
“…Recent hearing aid studies have verified the effects of the currently available technology and compared more sophisticated hearing aids with less sophisticated hearing aids used in the management of tinnitus (Trotter & Donaldson, 2008;Searchfield et al, 2010). Patients who used hearing aids combined with counseling obtained approximately twice the reduction in their tinnitus handicap than those who preferred only counseling (Aazh et al, 2009).…”
Section: Hearing Aids Fittingmentioning
confidence: 99%